Commentary is free: issue management and gaining capital with thought leadership - Prahl, Andrew (2023)
Expert commentaries are an avenue in which individuals and the organisations they represent position themselves on issues that are relevant to stakeholders. This paper considers the motivations for writing them, assessing this through two conceptual lenses: issue management and cultural, symbolic and economic capital. By writing an expert commentary an individual manages the way an issue is perceived and in doing so gains either immediate economic capital in the form of payment or symbolic or cultural capital which may in the future be converted into economic capital through increased career opportunities or promotion. We analyse expert commentaries in the Singapore news media and surveys their authors to investigate what prompted them to contribute their articles. We bring together (organisational) thinking on issue management and (individual) thinking on self-promotion as reflected in expert commentaries and suggest lessons for issue management through expert commentary.